Human rights violations committed by private military and security companies: an international law analysis - Karska, Elzbieta (Espaço Jurídico Journal of Law [EJJL], 2016)
Abstract: This paper is devoted to the growing phenomenon of the private military and security industry with respect to human rights obligations. In the first part, it will analyze the concept of a private security company, which is not clear in national regulations and has few relevant provisions in international conventions. The second part will contain a short description of examples of human rights violations committed by private military and security companies, or with their participation, during service delivery or other forms of activity. The third part of this paper discusses possible methods of responsibility enforcement, with respect to the transnational character of many private security companies involved in human rights violations worldwide. One of the most important elements of the discussion in international community should focus on binding international instrument, preferably a convention, which would be able to establish at least very elementary rules for states and international organizations, responsible for using private military and security companies. The international community has witnessed a lot of initiatives from non-governmental entities, also model laws and self-regulations of the private security industry, but still the real problem has not even been reduced. The number of human rights violations has grown.Keywords: Human rights. Private security companies. Liability.